(untitled) (Universal International Scientific Journal, 2026)
A competency assessment model suitable for digital learning environments in the teaching of nanotechnology in higher medical education is proposed. The model combines diagnostic testing, formative microassessment, e-portfolio, project, and final integrative assessment and serves to improve the quality of education.